A non-enzymatic sensor based on Au@Ag nanoparticles with good stability for sensitive detection of H2O2. (5th January 2016) - Li, Zhi; Zheng, Xiaohui; Zheng, Jianbin
Abstract : Synthesis of Au@Ag NPs by a seed-mediated growth procedure and fabrication of a non-enzymatic H2 O2 sensor. Abstract : Au@Ag nanoparticles (NPs) with good stability were prepared by a seed-mediated growth procedure in an aqueous solution of cetyltrimethylammonium chloride (CTAC) using spherical Au NPs as seeds. The as-prepared Au@Ag NPs were characterized by UV-visible spectroscopy and transmission electron microscopy (TEM), and further a nonenzymatic sensor was fabricated. The sensor exhibited excellent electrochemical performance towards H2 O2 reduction at −0.2 V with a linear range from 5.0 μM to 10.0 mM, a limit of detection of 1.3 μM and a high sensitivity of 116.7 μA mM −1 cm −2 in N2 -saturated phosphate buffer solution (PBS, pH 7.2). The results demonstrated that Au@Ag NPs promise to be a new platform for constructing H2 O2 biosensors.